Creating a Toponymic Map of the Middle Volga Region Based on the Materials of the P. S. Pallas Expedition of 1768–1769 - Razina S. Kuznetsova; Stepan A. Senator (Вопросы ономастики, 2021)
The paper presents a study of toponyms attested by Academician Peter Simon Pallas during his expedition in the Middle Volga region (on the territory of the modern Samara and Ulyanovsk regions) in 1768–1769. The study data is retrieved from his Travels to Different Provinces of the Russian State, published originally in the German language. The book has never been considered as a source on historical toponymy of the Middle Volga Region which explains the authors’ interest to it. The first part of the paper provides various linguo-statistical data on local toponyms found by Pallas: their distribution by types of geographical objects; phonetic, morphological, structural, and other changes that these place names have undergone over 250 years. The second part contains a toponymic map created from Pallas’s records. The map uses GIS technologies and contains information on the geographical distribution of the mentioned Middle Volga toponyms belonging to different cultural strata: most ancient are Iranian, later ones — Finno-Ugric and Turkic, and the latest are Slavic. On the one hand, these materials help restore the linguo-geographic picture of different ethnic groups formerly attested in the Middle Volga region, and on the other hand, they provide a basis for further linguistic research into the regional toponymy.